Nonlinear finite element modeling of reinforced concrete structural walls - Güllü, Muhammet Fetih. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
A relatively simple finite element modeling approach–referred to as the Fixed-Strut- Angle Finite Element (FSAFE) Model–is proposed in this thesis for simulating the hysteretic lateral load behavior of reinforced concrete (RC) structural walls with both flexural and shear controlled responses. The behavioral characteristics of the constitutive panel elements incorporated in the model formulation are based on a fixed-crack-angle modeling methodology. Improvements are made on the constitutive panel model formulation, with the implementation of simple behavioral models for shear-aggregateinterlock in concrete and dowel action on reinforcing bars. Model response predictions were first compared with experimentally-measured global and local responses of wall specimens with varying behavioral characteristics; including relatively slender (shear spanto- depth ratios between 2.3 and 3.0) flexure-controlled walls with rectangular and Tshaped cross-sections, as well as medium-rise walls (shear span-to-depth ratios between 1.5 and 2.0) with coupled shear-flexural responses. The FSAFE model formulation was further refined for improved simulation of walls with shear-controlled responses, with modifications made on the hysteresis rules of the shear aggregate interlock and dowel action models, as well as by incorporating cyclic degradation parameters in their constitutive formulation. The FSAFE model formulation was also modified for consideration of strain penetration effect within the wall foundation, and for limiting the strain localization effect. The improved model was validated against tests on RC squat wall specimens (shear span-to-depth ratios between 0.44 and 1.15) with shear-dominant responses, incorporating a variety of behavioral characteristics at global and local response levels. The proposed FSAFE model is shown to be a relatively simple yet accurate and reliable modeling approach for simulating nonlinear wall behavior, which can be used towards improvement of performance-based seismic design and assessment of methods for building structures incorporating RC walls.
Keywords: Reinforced concrete.; Structural analysis (Engineering); Finite element method.